Online Education at Voronezh State University - E. E. Chupandina; A. V. Semenikhina (Высшее образование в России)
The article describes the state of online learning at Voronezh State University and presents general information about its main components, such as e- library resources, electronic system for education process management, and  the university’s online courses. Since 2001 the University is a participant of  the scientific and technological program “Creation of the open education  system in the Russian Federation”. Within the framework of this program an  informational and educational portal Voronezh. OpeNet.ru − “Voronezh  virtual university” has been established, which is a part of the mega-portal of the Russian informational and educational environment of open education  (www.OpeNet.ru). In 2007 the University has started the work for  implementation of network education based on LMS Moodle. Online education is being realized on three levels: e-library resources,  organization of educational process (“Electronic University”), and online  courses (distant courses, university online courses, and open online courses).  Distant courses include 59 courses on ecology and learning  foreign languages worked out in the framework of Tempus project. At  present Voronezh State University is developing its own open online courses  (MOOC) using the experience of Tomsk State University and Moscow Institute of Physics and Technology. The implementation of online learning makes it  possible to realize two main principles of modern education − “education for  everybody” and “lifelong education”.